When marketing mirrors jazz: creativity during the mature stage of a product's life cycle. Issue 4 (11th April 2016) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Structured Abstract Findings: Marketers are a canny lot. Then again, they have to be. Their operating environment is invariably congested, so securing the attention of the public is rarely an easy task. Any lasting competitive edge will only be obtained by those able to constantly outwit their rivals. Marketing goes hand-in-hand with creativity. It might therefore be assumed that the best marketers are the most creative ones. This capability becomes even more valuable when it comes to findings ways of revitalizing ideas which have become stale in consumers' eyes. Author George Kneller articulated the essence of this when claiming that marketers must take a fresh look at what's familiar to them to think creatively. Practical Implications: The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.